Host factors associated to false negative and indeterminate results in an interferon‐γ release assay in patients with active tuberculosis - J.A. Santos; R. Duarte; C. Nunes (Pulmonology)
Introduction Information on host factors that contribute to false negative and indeterminate results in interferon‐γ release assays (IGRA) are critical to improve the usefulness of these tests in the fight against tuberculosis (TB) epidemics.The aim of this study was to estimate and compare the sensitivity of an IGRA and the tuberculin skin test (TST), independently and as a combined approach, in patients with TB and to identify risk factors associated with false negative and indeterminate IGRA results.Methods Retrospective cohort study of all active TB notifications with an IGRA result (n = 1230), from 2008 to 2015. 68.0 % (n = 727) of these patients had a TST result interpreted using a 5 mm (TST-5 mm) and 10 mm (TST-10 mm) cutoff. Sensitivity was determined for both tests.Logistic regression analysis was used to evaluate the association of sociodemographic and clinical factors to the risk of false negative or indeterminate IGRA results.Results IGRA, TST-5 mm and TST-10 mm were positive in 82.4 %, 84.5 % and 78.4 % of the patients that performed both tests. When used combined, IGRA/TST-5 mm sensitivity was 91.7 % and IGRA/TST-10 mm sensitivity was 90.6 %. Age≥65 years, alcohol abuse and pulmonary TB were predictive factors for indeterminate results. Inflammatory diseases and pulmonary TB were statistically associated with false negative IGRA results.Conclusion Inflammatory diseases and pulmonary TB were identified as factors for false negative IGRA results. Our results indicate that the use of both tests in a combined approach, especially in specific risk groups of the population, could increase the sensitivity of the screening process and accelerate the achievement of the WHO End TB Strategy goals.